Sosialisasi Implementasi ERP (Enterprise Resource Planning) iDempiere sebagai Sistem Informasi Keuangan PT. Swabina Gatra - Amalya Diva Andriyani; Muhadjir Anwar (Universitas Negeri Padang, 2023)
The technological transformation in the financial sector is crucial, particularly for companies like PT Swabina Gatra. The socialization and evaluation of the Enterprise Resource Planning (ERP) system at PT Swabina Gatra are inevitable steps to enhance understanding of ERP implementation in corporate financial management. The methods employed encompass user testimonials, practical demonstrations, discussion, and evaluation sessions to identify positive impacts, shortcomings, and challenges during the iDempiere ERP implementation, especially in financial aspects such as Financial Accountability (PJK), Direct Payment Requests (PPL), and Advance Payment Requests (PUM). The outcomes provide insights into the contributions and limitations of iDempiere ERP, along with solutions to enhance financial management practices, particularly in payment effectiveness and corporate fund allocation accountability. The technological transformation in the financial sector is not only vital for PT Swabina Gatra but is also expected to have a significant impact on society and Indonesia's overall economic growth